Ethics, solidarity and "Service Learning" in higher education - Arratia Figueroa, Alejandra (Acta Bioethica, 2008)
This paper explains the teaching experience of the "Service Learning" methodology, and it hopoes to point out the possibilities that it offers for the teaching of ethics, as well as for the stimulation of social responsability and to form values in the frame of curricular activities in nursing. This methodology searches to encourage, on one hand, students' compromised participation in the reaching-apprenticeship process and, on the other hand, to fortify the giving component of a good quality' component for the community. As an experienced pedagogical frame, it strengthens the critical thought and problema' resolutions, and it encourages a formal reflection during the experience.